Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

1)Complete study of the function

-monotony of the function -concavity -maximum and minimum -Zero of the function -if the function is ascending or descending -inflection points

2)make the primitive and find the area “under the curve” in a closed “interval” (break)

-Primitive-make the derivative -Calculate the area analytically and numerically in a closed interval

3) -average value [0;1]) -expected value -Variance -compare values for the exponential distribuition

share|cite|improve this question
So what have you done so far? What are your specific questions? – Ross Millikan Jan 10 '11 at 17:56
Note that the exponential distribution is of the form $\lambda e^{-\lambda x}$ were $\lambda = \frac{1}{\mu}$. – PEV Jan 10 '11 at 17:57
up vote 1 down vote accepted

More generally, consider the function $f(x;\theta)=(1/\theta)e^{-x/\theta}$, $x \geq 0$, where $\theta > 0$ is fixed, i.e. the density function of the exponential distribution with mean $\theta$. It is strictly decreasing and convex. $ \int {f(x;\theta )dx} = - e^{ - x/\theta } + C$, and $F(x): = \int_0^x {f(u;\theta )du} = 1 - e^{ - x/\theta } $, for any $x \geq 0$ (distribution function of exponential distribution); in particular $\int_a^b {f(x;\theta )dx} = F(b) - F(a) = e^{ - a/\theta } - e^{ - b/\theta } $. The corresponding expectation is $\int_0^\infty {xf(x;\theta )dx} = \theta $, and more generally, the corresponding $n$th moment is given, for all $n \in \mathbb{N}$, by $$ \mu'_n := \int_0^\infty {x^n f(x;\theta )dx} = \theta ^n \int_0^\infty {x^n e^{ - x} dx} = \theta ^n \Gamma (n + 1) = \theta ^n n!, $$ where $\Gamma$ denotes the gamma function. In particular, the corresponding variance is given, according to the formula ${\rm Var}(X)={\rm E}(X^2)-{\rm E}^2(X)$, by $\mu'_2 - (\mu'_1)^2 = 2 \theta^2 - \theta^2 = \theta^2$.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.